2016
DOI: 10.1097/brs.0000000000001292
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Nutrition Supply and Pathways on the Degenerative Patterns in Human Intervertebral Disc

Abstract: Study Design Investigation of the effects of the impairment of different nutritional pathways on the intervertebral disc degeneration patterns in terms of spatial distributions of cell density, glycosaminoglycan content, and water content. Objective To test the hypothesis that impairment of different nutritional pathways would result in different degenerative patterns in human discs. Summary of Background Data Impairment of nutritional pathways has been found to affect cell viability in the disc. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Above and below intervertebral discs, a layer of hydrated biological tissue exists, called the cartilaginous endplate (CEP). Since nucleus pulposus and annulus fibrosus tissues do not have their own vascular supply, the CEP is the main nutritional supply route for intervertebral discs . Loss of nutrient supply may lead to increased cell death, matrix degradation as well as decreased matrix production in intervertebral discs, which further lead to disc degeneration .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Above and below intervertebral discs, a layer of hydrated biological tissue exists, called the cartilaginous endplate (CEP). Since nucleus pulposus and annulus fibrosus tissues do not have their own vascular supply, the CEP is the main nutritional supply route for intervertebral discs . Loss of nutrient supply may lead to increased cell death, matrix degradation as well as decreased matrix production in intervertebral discs, which further lead to disc degeneration .…”
Section: Introductionmentioning
confidence: 99%
“…Since nucleus pulposus and annulus fibrosus tissues do not have their own vascular supply, the CEP is the main nutritional supply route for intervertebral discs . Loss of nutrient supply may lead to increased cell death, matrix degradation as well as decreased matrix production in intervertebral discs, which further lead to disc degeneration . Therefore, CEP dysfunction, which may block the nutritional supply for disc tissues, is believed to play a vital role in IDD pathogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…It seems that the appearance of the bright spot in the posterior region (Fig. 2b) may be related to the nutrition level in this particular region, 33 where the change in relative tissue volume (i.e., dilation) is found to be small (data not shown) and there is no cell death for the nutrition boundary condition in the case of mildly degenerated disc. This may be partially attributed to the relatively short diffusion distance between this region and nutrition supply source at the disc edge.…”
Section: Discussionmentioning
confidence: 94%
“…Intervertebral discs consist of cartilage endplate and nucleus pulposus (NP) and annulus fibrosus (AF) cells. Cartilage endplates are required for stress distribution and nutrient transport to the intervertebral discs (2,3). It has been reported that degeneration of the endplates may result in IDD (4,5).…”
Section: Introductionmentioning
confidence: 99%